Analisis Tingkat Kepuasan Pengguna Aplikasi Ojek Online Dengan Metode Naive Bayes - Wulan Dari; Elen Tania Hanayah (Yayasan Literasi Sains Indonesia, 2023)
In today's digital era, activities in various transportation service processes are increasingly sophisticated, which of course makes the implementation process easier. One example of the impact that can be felt is the presence of an online-based motorcycle taxi service which is the latest breakthrough in the development of technology and information in the field of transformation which is currently being increasingly used and favored by the public. Analyzing the level of satisfaction of online motorcycle taxi users also needs to be carried out, in order to find out how the public views the quality of services that have been provided by drivers. This study uses survey methods, literature studies and the application of the Naive Bayes algorithm. The results of this study are able to provide detailed explanations and elaborations regarding how the level of satisfaction is from the point of view of online motorcycle taxi service users and related to the indicators used using the Naive Bayes algorithm. From the results of this study, it is hoped that it can become a source of reference on how important it is to understand and implement the use of naive bates in making decisions from a number of data, one of which is in terms of determining the level of user satisfaction with what is provided by online motorcycle taxi drivers.